Report finds promise in SIFs based on Vancouver and Sydney - Knopf, Alison (Alcoholism & Drug Abuse Weekly, 2021)
Supervised injection facilities (SIFs) are promising in the reduction of opioid overdoses — at least in the only two sites in the world where they have been studied — according to a January report issued by the Institute for Clinical and Economic Review (ICER). The report, a literature search, noted that there are no randomized controlled trials that would make it possible to compare SIFs, currently illegal in the United States, with syringe services programs, which are not only legal in most states but can receive federal funding. The ICER did find that SIFs are associated with a reduction of opioid overdoses in Vancouver, Canada, and Sydney, Australia. Whether they should open in the United States as a way to combat opioid overdose deaths is a subject of controversy. We asked Beau Kilmer, Ph.D., McCauley Chair in Drug Policy Innovation at RAND and director of the RAND Drug Policy Research Center, a top expert in the United States on the topic, to review the executive summary for us, which he kindly did. “I think they did a good job of highlighting (1) the issues with generalizability — the vast majority of the published research comes from two sites, and most of this research was conducted before illegally produced fentanyl hit the streets — and (2) the lack of strong research designs in many of these studies,” he told ADAW. Another review of the literature, published in Addiction in 2019, for which Kilmer was corresponding author, concluded: